Reduced Serological Response to COVID-19 Vaccines in Patients with IBD is Further Diminished by TNF Inhibitor Therapy; Early Results of the VARIATION study [VAriability in Response in IBD Against SARS-COV-2 ImmunisatiON]. (18th February 2022) - Doherty, Jayne; Morain, Neil O; Stack, Roisin; Girod, Parker; Tosetto, Miriam; Inzitiari, Rosanna; Sheridan, Juliette; Cullen, Garret; McDermott, Edel; Buckley, Maire; Horgan, Gareth; Mulcahy, Hugh; et al.
Abstract: Background and Aims: Evidence suggests patients with inflammatory bowel disease [IBD] receiving TNF antagonists have attenuated response to vaccination against COVID-19. We sought to determine the impact of IBD and of various medications for treatment of IBD on antibody responses to vaccination against COVID-19. Methods: Patients with IBD [ n = 270] and healthy controls [HC, n = 116] were recruited prospectively, and quantitative antibody responses were assessed following COVID-19 vaccination. The impact of IBD and of medications for treatment of IBD on vaccine response rates was investigated. Results: Of HC, 100% seroconverted following complete vaccination with two vaccine doses; 2% of patients with IBD failed to seroconvert. Median anti-spike protein [SP] immunoglobulin [Ig]G levels following complete vaccination in our IBD cohort was significantly lower than among HC [2613 AU/mL versus 6871 AU/mL, p ≤0.001]. A diagnosis of IBD was independently associated with lower anti-SP IgG levels [β coefficient -0.2, p = 0.001]. Use of mRNA vaccines was independently associated with higher anti-SP IgG levels [β coefficient 0.25, p ≤0.001]. Patients with IBD receiving TNF inhibitors had significantly lower anti-SP IgG levels [2445 AU/mL] than IBD patients not receiving TNF inhibitors [3868 AU/mL, p ≤0.001]. Patients with IBD not receiving TNF inhibitors still showed attenuated responses compared with HC [3868 AU/mL versus 8747 AU/mL, p = 0.001]. Conclusions: Patients with IBD have attenuated serological responses to SARS-CoV-2 vaccination. Use of anti-TNF therapy negatively affects anti-SP IgG levels further. Patients who do not seroconvert following vaccination are a particularly vulnerable cohort. Impaired responses to vaccination in our study highlight the importance of booster vaccination programmes for patients with IBD.